2021
DOI: 10.3390/vaccines9090949
|View full text |Cite
|
Sign up to set email alerts
|

Role of NKT Cells during Viral Infection and the Development of NKT Cell-Based Nanovaccines

Abstract: Natural killer T (NKT) cells, a small population of T cells, are capable of influencing a wide range of the immune cells, including T cells, B cells, dendritic cells and macrophages. In the present review, the antiviral role of the NKT cells and the strategies of viruses to evade the functioning of NKT cell have been illustrated. The nanoparticle-based formulations have superior immunoadjuvant potential by facilitating the efficient antigen processing and presentation that favorably elicits the antigen-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 109 publications
(146 reference statements)
1
14
0
Order By: Relevance
“…The initial cytokine drugs approved by the FDA were IFNα-2a (Roferon-A) and IFNα-2b (Intron-A). Subsequently, high doses of IL-2 (Proleukin) were approved for the clinical treatment of metastatic melanoma and renal cancer ( Khan et al, 2021 ). In addition, the immune-adjuvant class is not antigenic per se but enhances the stimulation of the body’s immune system by antigen.…”
Section: Immunotherapymentioning
confidence: 99%
“…The initial cytokine drugs approved by the FDA were IFNα-2a (Roferon-A) and IFNα-2b (Intron-A). Subsequently, high doses of IL-2 (Proleukin) were approved for the clinical treatment of metastatic melanoma and renal cancer ( Khan et al, 2021 ). In addition, the immune-adjuvant class is not antigenic per se but enhances the stimulation of the body’s immune system by antigen.…”
Section: Immunotherapymentioning
confidence: 99%
“…Recent advances in the field of nanotechnology-based vaccine delivery systems have provided great promises in the development of effective vaccines that can induce strong immune responses. Certain nanoparticles such as liposomes, microspheres, and chitosan-nanoparticles have demonstrated potent vaccine carriers and immune-adjuvant actions [13,14]. A vaccine is considered effective in protecting against viral infections if it has the ability to induce antigen-specific antibody and cell-mediated immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes composed of E. coli lipids (Escheriosomes) and loaded with Salmonella typhimurium antigens induced the generation of the cytotoxic T lymphocyte (CTL) responses that effectively protected mice against bacterial infection [ 21 ]. The superior immunoadjuvant potential of liposomes can be inferred from their unique property of they can deliver the encapsulated antigens to the intracellular compartments of antigen-presenting cells (APCs) that can induce both CD4+ and CD8+ T cells [ 22 ]. None of the earlier studies showed the prophylactic efficacy of the liposome-based vaccine against A. baumannii infection in model animals.…”
Section: Introductionmentioning
confidence: 99%